Ameliorative effect of rosiglitazone, a peroxisome proliferator gamma agonist on adriamycin‐induced cardio toxicity via suppressing oxidative stress and apoptosis. Issue 4 (29th October 2019) - Zhang, Lingling; Wu, Ping; Zhang, Luyan; SreeHarsha, Nagaraja; Mishra, Anurag; Su, Xinyou
Abstract: We investigated the rosiglitazone (RSG) effect on adriamycin (ADM)‐induced cardio toxicity in experimental animals. Forty adult Wistar male rats were separated into four groups as follows: normal control; RSG (10 mg/kg)‐treated; ADM (10 mg/kg)‐administered; and ADM (10 mg/kg) + RSG (10 mg/kg)‐treated. Serum lipid level, different biochemical biomarkers, histological analysis, and nuclear factor erythroid 2‐related factor/heme oxygenase‐1 (Nrf2/HO‐1), Caspase 3, B‐cell lymphoma 2 (Bcl‐2), and Bax gene expression were assessed in serum and cardiac tissue samples. Our results show that RSG treatment in ADM‐administered animals significantly diminished low‐density lipoprotein cholesterol, triglyceride, and total cholesterol, and increases high‐density lipoprotein cholesterol (HDL‐c) in comparison with the ADM group. RSG treatment reduced the effect of ADM administration on cardiac dysfunction markers such as cardiac troponin T Creatine Kinase‐MB, aspartate aminotransferase, and lactate dehydrogenase, showing the amelioration of cardio toxicity in ADM‐administered rats. Additionally, RSG treatment significantly decreased the level of malondialdehyde and nitric oxide in cardiovascular tissue. RSG‐treated rats in combination with ADM likewise showed a significant increase in reduced glutathione, superoxide dismutase, catalase content, and the activity of glutathione peroxidase (GPx) as compared with ADM group. Moreover, RSG treatment in ADM rats significantly increased an Nrf2 and HO‐1 expression in comparison with ADM group. While in apoptosis parameters, RSG treatment in ADM rats significantly diminished a cleaved caspase‐3 and Bax expression as well as expanded Bcl‐2 expression when contrasted with ADM group of rats. In conclusion, RSG is capable of protecting heart toxicity in ADM‐treated animals through defensive effects on oxidative stress and biochemical markers.